Pondasi Kebijakan Pembangunan IKN Dalam Mencapai Indonesia Emas 2045 - Rusyono, Ono (CV. Green Publisher Indonesia, 2025)
This research explores the role of IKN development in fostering development and progress in the economic, development and human resources sectors. The development of the sector must be supported by strong policy regulations and adequate budgets, development in all sectors and implemented equally in the country based on the principles of justice and wisdom. In this study, the three sectors are the key to building a new IKN in achieving a Golden Indonesia in 2045. This research uses a literacy-based qualitative method, which is a research approach that uses written sources, such as books, scientific articles, online and print news, documents, and other literature, as the main data source in analyzing the pillars of IKN development. This method is often used to understand social, cultural, or historical phenomena through the interpretation of the text and its context. This research results that the foundation of development and equity interpreted by the implementation of IKN development shows the suitability of the planned development system, first, the government has made and ratified administrative regulations for infrastructure and human resource development as a legal basis in planning and implementing development, second, the government's efforts in implementing budget efficiency and effectiveness strategies to be allocated on development funding and priority programs. Third, government programs to reduce poverty rates and low human resource development have helped more community needs as well as an answer to the government's role and responsibility in alleviating poverty and increasing the human development index.